A Rare Case of Aortomesenteric Clamp Syndrome in a 14-Year-Old Adolescent - Lalaoui, Karima; Djelad, Mohamed; Benzaoui, Reda; Ouslim, Rachid (International Journal of Scientific Research and Management (IJSRM), 2024)
Aortomesenteric clamp syndrome (SPAM) or Wilkie syndrome results from compression of the third duodenum between the superior mesenteric artery and the aorta; it is a rare entity, especially in children. The symptomatology resulting from this duodenal obstruction is that of a high occlusion. The diagnosis is based on CT angiography which may or may not be coupled with ingestion of water (or iodinated contrast product). The treatment is primarily medical, it is based on the installation of a nasogastric tube; correction of hydroelectrolyte disorders and parenteral or enterojejunal nutrition. Surgery is only indicated if medical treatment fails. In this work, we report our experience in caring for a 14-year-old adolescent with SPAM.